Surface modified solution‐derived nickel oxide film via ion‐beam irradiation as a liquid crystal alignment layer. Issue 12 (15th July 2019) - Lee, Ju Hwan; Won, Jonghoon; Jeong, Hae‐Chang; Kim, Dong Hyun; Lee, Dong Wook; Song, In Ho; Oh, Byeong‐Yun; Han, Jeong‐Min; Kim, Dai‐Hyun; Seo, Dae‐Shik
Abstract: In this article, we demonstrate the liquid crystal (LC) alignment characteristics of solution‐derived nickel oxide (NiO) film modified with ion‐beam (IB) irradiation. Cross‐polarized optical microscopy and pretilt angle measurements verified that uniform LC alignment was achieved using the NiO film as an alignment layer regardless of IB incidence angle. Contact angle measurements revealed that all of the NiO films had a deionized water contact angle below 90°, which indicates that they had hydrophilic surfaces that had an effect on the homogeneous LC alignment. Atomic force microscopy was conducted to determine the physical surface modification due to the IB irradiation, which showed that it reduced the size of the surface grains with agglomerations depending on the surface tilt from the IB incidence angle. Furthermore, microgroove structures strongly related to uniform LC alignment were observed after IB irradiation. Chemical surface modification was investigated via an X‐ray photoelectron spectroscopy analysis which revealed that IB irradiation modified the chemical bonds in the NiO film, and this affected the LC alignment state. Thus, these results indicate that using NiO film exposed to IB irradiation as an alignment layer is a suitable method for LC applications. Abstract : Using ion‐beam (IB) irradiation on solution‐derived nickel oxide (NiO) film at various incidence angles, uniform and homogeneous liquid crystal (LC) alignment was achieved. Through contact angle measurement, it was revealed that all NiO films had a hydrophilic surface which is strongly related to homogeneous LC alignment. Furthermore, physicochemical surface modification due to IB irradiation was verified.